Enhancing Students’ Mathematical Thinking through Math Journal - A. Belango, Manuel; G. Carag, Catalina (International Journal of Psychosocial Rehabilitation, 2020)
This quasi-experimental study focused on the investigation of the effectiveness of math journals in the teaching of mathematics in the modern world, particularly in enhancing mathematics performance among first-year Bachelor of Elementary Education students of Cagayan State University, Andrews Campus, Tuguegarao City, for the second semester of the 2018-2019 school year. This study ascertained that journal entries in mathematics are valuable in providing opportunities for students to acquire substantial knowledge and coherent understanding of mathematics concepts by communicating their learning in their own words. Thus, the integration of math journals in teaching significantly enhanced communication skills, mathematical thinking, and the performance of students in mathematics. The paper also disclosed that journal activities provide the students with opportunities to develop a broader understanding of the various concepts in mathematics and learn to communicate how they feel about the learning environment. Moreover, the math journal provides an avenue for students to undergo the process of self-reflection and self-assessment. Hence, through the diverse math journal activities, the learning of mathematics becomes more meaningful and interesting.